2005
DOI: 10.1088/0953-2048/18/8/010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gd2Ba4CuMoOyaddition on the band structure and spatial variation of superconducting properties in GdBa2Cu3O7−δsingle domains

Abstract: Gd2Ba4CuMoOy (Gd2411) single phase was synthesized in air and added into GdBa2Cu3O7−δ (Gd123) bulk superconductors with the addition amount ranging from 0.2% to 20%, in molar ratio to Gd123. Both microstructure and superconducting properties of each bulk were investigated from the seed position to the boundary of a single domain. Although a band structure with the alternative distribution of Gd2BaCuO5 (Gd211) and Gd2411 appeared in all samples, the range of this inhomogeneity only appeared within 5 mm from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…The second phase rich and diluted bands alternatively distributed and this kind of band structure appeared in all the bulks with Gd2411 addition in our study, even 0.002 Gd2411 [9]. But this kind of band structure only appears within 5 mm from each side of the seed.…”
Section: Gd211/gd2411 Distribution Inside Gd123 Bulksmentioning
confidence: 41%
“…The second phase rich and diluted bands alternatively distributed and this kind of band structure appeared in all the bulks with Gd2411 addition in our study, even 0.002 Gd2411 [9]. But this kind of band structure only appears within 5 mm from each side of the seed.…”
Section: Gd211/gd2411 Distribution Inside Gd123 Bulksmentioning
confidence: 41%
“…The mixed powders were pressed into pellets with 20 mm in diameter and 8 mm in thickness. The melting process of the bulk superconductors and the post-annealing in argon and oxygen gases have been reported elsewhere [2,8].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, RE 2 Ba 4 CuMO y (M = Nb, Ta, Mo, W, Re, Zr and Hf) [7,8] as second phase with RE211 have successfully fabricated single grain RE123 bulk. It is observed that RE2411 inclusions can embed in the superconductor matrix in nano-size and form effective magnetic flux pinning sites to increase J C .…”
Section: Introductionmentioning
confidence: 99%
“…In many research center, various kinds of chemical doping, including metal and nonmetal elements particles of magnetic alloys [13][14][15][16], various insulating particles such as RE 2 BaCuO 5 (RE211) and RE 2 Ba 4 CuO 5 (RE-2411) and other nonsuperconducting particle have been used as secondary phase particles which can be act as pinning centers in bulk HTS superconductors [17][18][19]. It is well known that, compared to YBa 2 Cu 3 O y−ı the (LRE)Ba 2 Cu 3 O 7−ı superconductors, where LRE is a light rare earth element, such as La, Nd, Sm, Eu and Gd, attract important attention as a consequence of their higher superconducting transition temperature (T c ) and critical current density (J c ), especially in medium and strong magnetic fields.…”
Section: Introductionmentioning
confidence: 99%